Analisis Perkembangan Dan Resistansi Sukuk Korporasi Dalam Produk Pasar Modal - Muhammad Anwar Rifa'i; Rois Ibnu Sina (UIN Siber Syekh Nurjati Cirebon, 2019)
The financial crisis that has occurred so far according to experts is a result of the interest system that occurs in capital market and banking products. Therefore it is necessary to bring up systems and instruments that avoid the form of interest in which the interest in Islam is called usury, and the law is haraam. One instrument that carries a non-interest system is sukuk, the sukuk discussed in this study is corporate sukuk issued by well-known companies in Indonesia.This study aims to analyze how the Development and Resistance of Corporate Sukuk in Capital Market Products with qualitative descriptive methods. The analysis used is analysis of opportunities, threats, strengths and weaknesses or SWOT. The results of the study found that the strategy of implementing corporate sukuk in Indonesia still had a considerable opportunity even though in 2019 it was predicted to be sloping. The parties are expected to be able to work together and have good commitment in minimizing weaknesses and threats.Key words: Corporate Sukuk, Islamic Economy, Capital Market, SWOT Analysis.Â